Radio Frequency Interference Observations at IAR La Plata - Haze, Hayo (2013)
The Wettzell RFI-Monitoring system was developed to monitor radio frequency interference at existing and potential VLBI sites. It is a transportable system which can be operated in a semiautomated manner. It was used at the Instituto Argentino de Radioastronomía in La Plata to investigate a future site for the Transportable Integrated Geodetic Observatory (TIGO). With the help of an automated pedestal for the RFI-monitoring antenna a 24h/7d survey was conducted during September and October 2012. This data set is one of the most dense RFI-monitoring samples known within the IVS. The results of this survey showed, that most of the present RFI signals occure sporadically and take away less than 5% of the observation time. Hence IAR is a suitable site for TIGO.